Paramagnetism of carbyne nanocrystals. (March 2021) - Yang, Fei; Liu, Pu; Wu, Changwei; Yao, Dao-Xin; Yang, Guowei
Graphical abstract: Abstract: In terms of carbon-atom hybridization, well-established forms of carbon are diamond with three-dimensional sp 3 -hybridization and graphite with two-dimensional sp 2 -hybridization which have been known as the first and second carbons and utilized for millennia. In fact, there is the third carbon with one-dimensional sp -hybridization, i.e. so-called carbyne. Recently, nanocrystals of the third carbon have been synthesized in the laboratory and they are called white carbon because these synthesized carbyne nanocrystals (CNCs) look white powders. Here, for the first time, the paramagnetism of CNCs is reported. Experimental observations show notable paramagnetism but no magnetic ordering at any given temperature. The moment concentration is estimated to be one moment per approximately 10, 000 carbon atoms. These magnetic moments are probably originated from the collective magnetism phenomenon, which is attributed to hydrogen atom adsorbed on the carbon chain and vacancy in CNCs according to density functional theory-based first principle calculations. The localized defect wave favors a spin-polarized ground state and forms a local magnetic moment, promoting a long-range magnetic coupling between local magnetic moment, finally, results in a collective magnetism. This understanding about magnetism and its origin in the sp -hybridized carbon material can be instructive to interpretation of magnetism of other carbon allotropes.